Non-surgical Techniques for Combined Rheumatic Severe Aortic and Mitral Stenosis – Case Series and Brief Review of Literature - Karuru, Uma Devi; Tummala, Sadanand Reddy; T, Naveen; Kanjerla, Kiran Kumar; PS, Gautam; Mysore, Sai Kumar (Journal of Cardiology and Cardiovascular Medicine, 2024)
Rheumatic heart disease persists as a significant concern in developing regions, often resulting in multivalvular heart conditions. Treatment options are limited, though percutaneous transvenous mitral commissurotomy effectively addresses rheumatic mitral stenosis. Non-surgical interventions for aortic stenosis include balloon aortic valvotomy and Transcatheter aortic valve replacement (TAVR), tailored to patient factors like age and comorbidities. We describe two cases of Rheumatic multivalvular disease which were managed non-surgical. The first case is a pioneering procedure performed on a young patient combined percutaneous transvenous mitral commissurotomy with balloon aortic valvotomy, guided by 4-dimensional transoesophageal echocardiography (4D TEE). This represents the first documented instance in medical literature, showcasing the potential of integrated interventions and advanced imaging techniques. In the second challenging case involving a heavily calcified, retrovirus, and Hepatitis B positive 55-year-old, a staged approach was adopted, involving percutaneous transvenous mitral commissurotomy followed by Transcatheter aortic valve replacement (TAVR). Despite complexities, this sequential strategy demonstrates the adaptability of transcatheter techniques in managing complex valvular pathologies. These cases highlight the evolving landscape of interventional cardiology and underscore the importance of tailored, multidisciplinary approaches in optimizing outcomes for patients with rheumatic heart disease and multivalvular involvement, especially in resource-limited settings. Further exploration and dissemination of such innovative strategies hold promise for enhancing cardiac care quality and expanding treatment options globally.